Early immune profiling reveals distinct inflammatory responses between children and adults few days after primary SARS-CoV-2 infection - Van de Garde, Martijn D. B.; Miranda-Bedate, Alberto; Nanlohy, Nening M.; Jacobi, Ronald H. J.; Meijer, Adam; Reukers, Daphne F. M.; Van Beek, Josine; Van Els, Cecile A. C. M.; Van Baarle, Debbie; Rots, Nynke Y.; De Wit, Jelle; Pinelli, Elena (Frontiers in Immunology, 2024)
BackgroundTo date, it is still not clear why during the COVID-19 pandemic children generally developed no or milder symptoms compared to adults. As innate immune responses are crucial in the early defense against pathogens, we aimed at profiling these responses from both adults and children with a primary SARS-CoV-2 infection.MethodsIn the first months of the pandemic, PBMCs and serum were collected from peripheral blood of adults and children at different time points after testing SARS-CoV-2 PCR positive (PCR+). The levels of SARS-CoV-2 Spike-specific IgG were measured in serum. The cells were cultured for 24 hours in medium only, with heat inactivated SARS-CoV-2 (iSARS-CoV-2) or toll-like receptor (TLR) ligands. The levels of secreted cytokines/chemokines as well as monocyte phenotype were determined.ResultsFew days after testing PCR+, PBMCs from PCR+ children secreted higher levels of cytokines/chemokines compared to PCR+ adults, after these cells were incubated either in medium only or after stimulation with iSARS-CoV-2 or TLR ligands. Furthermore, PBMCs from children stimulated with iSARS-CoV-2 secreted significantly higher levels of IL-10 and GM-CSF compared to PBMCs from control children. In contrast, PBMCs from the PCR+ adults secreted lower levels of IL-8 compared to adult controls. Phenotypic analysis of monocytes indicates a smaller proportion non-classical monocytes for adults compared to children. The distinct cytokine profiles, symptom severity, and the proportion of non-classical monocytes correlated to each other. The levels of Spike-specific IgG overtime did not significantly differ between children and adults.ConclusionsWithin the first week after testing PCR+, children showed a stronger inflammatory innate immune profile and experienced less severe symptoms compared to adults. Our data implies correlations between the secretion of cytokines/chemokines, proportion of non-classical monocytes, and symptoms severity. These findings enhance our understanding of the distinct pediatric and adult innate immune profile after SARS-CoV-2 infection and contributes to the knowledge necessary to improve future prevention strategies.